2021
DOI: 10.21203/rs.3.rs-421529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosomes derived from bone marrow mesenchymal stem cells promote angiogenesis via transfer of miR-21-5p after cerebral ischemia in mice

Abstract: Background Mesenchymal stem cells (MSCs) transplantation is a potential clinical therapy for cerebral ischemia. The therapeutic effects of MSCs primarily depends on the paracrine action by releasing exosomes (Exos). Exosomes derived from bone marrow mesenchymal stem cells (BMSC-Exos) could modulate target cell functions by transferring microRNAs (miRs) cargo. In this study, we aimed to investigate whether BMSC-Exos could promote angiogenesis via transfer of miR-21-5p after cerebral ischemia. Methods BMSC-Exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…MiR-486 released by adipose-derived stem cell-derived EV could mediate wound healing and promote angiogenesis [ 39 ]. MiR-21-5p could promote angiogenesis in the unilateral anterior crossbite model and MCAO model [ 40 , 41 ]. More importantly, the miR expression profile of BMSC-Exos confirmed that let-7i-5p, miR-21-5p, miR-22-3p, and miR-486 were abundant in BMSC-Exos [ 21 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-486 released by adipose-derived stem cell-derived EV could mediate wound healing and promote angiogenesis [ 39 ]. MiR-21-5p could promote angiogenesis in the unilateral anterior crossbite model and MCAO model [ 40 , 41 ]. More importantly, the miR expression profile of BMSC-Exos confirmed that let-7i-5p, miR-21-5p, miR-22-3p, and miR-486 were abundant in BMSC-Exos [ 21 , 42 ].…”
Section: Discussionmentioning
confidence: 99%